The Effect of Cofactor Binding on the Conformational Plasticity of the Biological Receptors in Artificial Metalloenzymes: The Case Study of LmrR - Alonso-Cotchico, Lur; Rodríguez-Guerra Pedregal, Jaime; Lledós, Agustí; Maréchal, Jean-Didier (Frontiers in Chemistry, 2019)
The design of Artificial Metalloenzymes (ArMs), that result from the incorporation of organometallic cofactors into biological structures, has grown steadily in the last two decades and important new-to-Nature reactions have been reached. This type of exercises could highly benefit from understanding the structural impact that the inclusion of organometallic moieties may have on the biological host. To date though, our understanding of this phenomenon is highly partial. This lack of knowledge is one of the elements that condition that first-generation ArMs generally display relatively poor catalytic profiles. In this work, we approach this matter by assessing the dynamics and stability of a series of ArMs resulting from the inclusion, via different anchoring strategies, of a variety of organometallic cofactors into the Lactoccocal multidrug resistance regulator (LmrR) protein. To this aim, we couple standard force field based techniques such as Protein-Ligand Docking and Molecular Dynamics simulations with a variety of trajectory convergence analyses able to assess both the stability and flexibility of the different systems under study upon binding of the cofactors. Together with the experimental evidences obtained in other studies, we provide an overview about how these changes can affect the catalytic outcomes obtained from the different ArMs. Fundamentally, our results show that the convergence analysis used in this work can assess how the inclusion of synthetic metallic cofactors in protein condition different structural modulations of their host. Those conformational modification are key to the success of the desired catalytic activity and their proper identification can be wisely use to improve the quality and the rate of success of the ArMs even for their first generation.